If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 4a = 7a Solving 15 + 4a = 7a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7a' to each side of the equation. 15 + 4a + -7a = 7a + -7a Combine like terms: 4a + -7a = -3a 15 + -3a = 7a + -7a Combine like terms: 7a + -7a = 0 15 + -3a = 0 Add '-15' to each side of the equation. 15 + -15 + -3a = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -3a = 0 + -15 -3a = 0 + -15 Combine like terms: 0 + -15 = -15 -3a = -15 Divide each side by '-3'. a = 5 Simplifying a = 5
| -3.8x+1.2=-17.8 | | 35-8=x | | 9x^2-2=o | | n+2=-14-na | | (1+2)+0= | | 3x=5x+70 | | 3-1.5(x+1)=6x-9 | | 63x^3+11x^2=-36x | | 20+1.25n=2.50n | | 121=100+0.3x | | -8x-3+9x=-9x+3 | | 6(b-a)=2(4a-3b) | | 8x+10=6x+90 | | 205+205+205= | | 0=-16x^2+96x+640 | | 4(x+1)-5(3-x)=14x-2(5x-3) | | 7-4(s-3)=23 | | .5x+3x+(2x+4)= | | 5=-16t^2+45t+6 | | 12x-108=-4x+36 | | 3x=2(-3)-18 | | 5u^2=-26u-5 | | 30=8+2(a+2) | | 12x+3=-7x+22 | | 12x+6=5(3x-2) | | 8x+40=-4x-68 | | 3-7x=8-5x | | 12x+3=-7x | | 14-5y-2y=19 | | -7x-5=-8x+7 | | 3(3-U)+1=31 | | (28b-2)-9(3b+2)=-5 |